Cultural factors associated with the management of breast lumps amongst Xhosa women - Nosipho Mdondolo; Louise de Villiers; Valerie J Ehlers (AOSIS, 2003)
A qualitative research design and an ethno-nursing research method were used to identify cultural factors influencing Xhosa women's health seeking behaviours associated with breast lumps. Opsomming 'n Kwalitatiewe navorsingsontwerp en 'n etnoverpleegkundige navorsingsmetode is gebruik. Die doel was om te bepaal watter kulturele faktore Xhosa vroue se strewe na welstand, wat in verband staan met 'n borsvergroeisel, beïnvloed. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.